“Análisis de la cadena productiva del maiz amarillo duro ( Zea mays L.) en la region de San Martín” - Armas Ugarte, Sandra (2004)
Present study has as an objective to analyse the Productive Chain of Hard Yellow Corn in the Region San Martin; employing as a tool of analysis the method of Porter's Value Chain which analysed the production and trading into Region San Martin. Also it was considered FODA analysis to evaluate the half-view of sector, which conducted us to elaborating development strategies, finally used the method of the Five Porter's Competitive Forces, as a determining factor of sector competitivity. After realizing a description and analysis to international, national and regional level of cornfarmer sector, analysed the value chain; producers have limited knowledge of market, deficient agricultura! handling on cultivation and postharvest, seed and raw material access problems, and scarse organization of producers. Production volumes of trading and processing enterprises are insufficient to be able keeping on representative-dealer power in the market. Gross margin of trading (GMT) to leve! of producers is of 16.67% with traditional sowing, 31.52% with direct sowing, and 29.18% with minimum tillage machined by under irrigation. To level of rural collector the GMT was of 11.11%. For intermediaries and traders the GMT was 6.25% and 11.76% respectively in the inter and extra regional market; finally for processing enterprises of balanced food the GMT was of 31.82% and 81.09% to poultry. Global efficiency determined as for average yielding per hectare into Region was below national average, covering 56.94% on national yielding and global efficiency on paid price to the farmer of region was 21.57% lower on paid price to national level. With respect to the half-view of cornfarmer sector of Region San Martin exist comparative advantages: able soils, favorable climate conditions, human resources enabled for agricultura! handling, improved variety, among other advantages that heeding adequately we can get the competitivity. According to the analysis of competitive forces: introduction of a new industrial and/or poultry plant is not a menace to the sector; industrial rivalry is minimum and sums up on competence for acquiring grain of good quality with a good price in production areas; dealer power of suppliers is great than a cornfarmer; competitivity of producer reflects on grain quality that offer, involving post-harvest handling; menace for the sector consists substitute products; to national level considers for the imported maize from USA, Argentina, Bolivia and Brasil, and menace to regional level, will present by saturation of production that added this the importation will be affecting to the producer fundamentally on product price.